Interim Singapore guidelines for basic and advanced life support for paediatric patients with suspected or confirmed COVID-19 - Gene Yong-Kwang Ong; Beatrice Hui Zhi Ng; Yee Hui Mok; Jacqueline SM Ong; Nicola Ngiam; Josephine Tan; Swee Han Lim; Kee Chong Ng (Singapore Medical Journal)
The COVID-19 pandemic has resulted in significant challenges for the resuscitation of paediatric patients, especially for infants and children who are suspected or confirmed to be infected. Thus, the paediatric subcommittee of the Singapore Resuscitation and First Aid Council developed interim modifications to the current Singapore paediatric guidelines using extrapolated data from the available literature, local multidisciplinary expert consensus and institutional best practices. It is hoped that this it will provide a framework during the pandemic for improved outcomes in paediatric cardiac arrest patients in the local context, while taking into consideration the safety of all community first responders, medical frontline providers and healthcare workers.